Integration of Islamic education management philosophy in a multicultural context - Hazaa, Zuhair Mubarrak; Nurhalimah , Nurhalimah; Anggraini, Yenita; Putri , Dinda; Dahlan, Zaini (Al-Misbah (Jurnal Islamic Studies), 2025)
This research aims to examine the role of Islamic multicultural education in addressing the growing challenges of intolerance and radicalism in Indonesia’s modern era. The study focuses on universal values such as tolerance, justice, and harmony, as emphasized in Islamic teachings. A descriptive qualitative approach was used, involving analysis of religious literature, educational policies, and practices in modern pesantren. The findings indicate that Islamic multicultural education grounded in the principles of tawhid and inclusiveness not only promotes respect for cultural, religious, and ethnic diversity, but is also effective in preventing social conflict. Pesantren that uphold the motto “above and for all groups” serve as concrete examples of these values in practice. This concept aligns with Qur’anic principles, such as QS. Al-Hujurat:13 and QS. Al-Anbiya:107, which highlight the importance of harmony and mutual understanding. The study concludes that Islam-based multicultural education holds significant potential to foster a harmonious, tolerant, and respectful society, making it highly relevant for addressing the challenges of diversity in the modern era. Its implementation can serve as a model for a national education system oriented towards inclusiveness and social justice.